Bank Soundness and Firm Value under the RGEC Framework - Yupita, Dian; P. D’Yan Yaniartha Sukartha (E-Jurnal Akuntansi, 2026)
Bank soundness is integral to firm value, reflecting a bank’s financial stability, risk management capacity, and profitability. This study investigates the association between bank soundness and firm value using the RGEC framework—comprising risk profile, good corporate governance, earnings, and capital—over the period 2011–2022. The analysis draws on 47 annual reports sourced from Refinitiv Eikon. Firm value is modeled as a function of the RGEC components, with revenue and total assets included as control variables. Grounded in signaling theory, the study employs multiple linear regression to examine the relationship. The findings reveal that good corporate governance, earnings, and capital are positively associated with firm value, whereas the risk profile exhibits a negative association. These results suggest that stronger governance, profitability, and capital adequacy, alongside lower risk exposure, enhance a bank’s long-term value by signalling resilience and operational soundness.